Healthcare providers’ utilization and perception on telemedicine: urgency amidst COVID-19 pandemic - Silvalena Silvalena; Rizma Adlia Syakurah (International Journal of Public Health Science (IJPHS), 2022)
The outbreak of coronavirus disease 2019 (COVID-19) in Indonesia had awakened the fact that the country’s healthcare system could not stand-alone with conventional in-person healthcare service. The sudden massive adaptation of telemedicine in Indonesia still needed be reassess periodically, especially with blooming numbers of users. This cross-sectional study conducted on medical doctors, dentists, and specialist in Indonesia, aimed to evaluate the utilization and perception of healthcare providers towards telemedicine in Indonesia during COVID-19 pandemic. Data were collected using convenience sampling from an online questionnaire through social media from June 16-29, 2020. Data were analyzed using Chi-square test (p-value<0.05) and prevalence ratios (PR) with 95% confidence interval (CI). Most physicians who practiced using telemedicine admitted that they used telemedicine as an alternative during pandemic (71.2%). The usage of telemedicine had an association with the idea that telemedicine provided the patients’ needs (p<0.001, 95% CI=3.53 (1.86-6.70) and provided knowledge for the society (p=.047 95% CI=3.54 (0.93-13.51)). The potential and benefits of telemedicine could be recognized during the pandemic, though the use of collaborative media and the advancement of platform features for a better quality of diagnosis could be improved The policymakers and stakeholders expected to establish a balanced and thoughtful framework of telemedicine.